2012
DOI: 10.2139/ssrn.2127568
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Disability Gap in Employment Rates in Developing Countries?

Abstract: This paper examines differences in employment rates between persons with and without disabilities in 15 developing countries using the World Health Survey. We find that people with disabilities have lower employment rates than persons without disabilities in nine countries. Across countries, disability gaps in employment rates are more often found for men than women. The largest disability gap in employment rates is found for persons with multiple disabilities. For countries with a disability gap, results from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 36 publications
4
69
2
Order By: Relevance
“…Mizunoya and Mitra (2013) assessed the employment gaps in fifteen low-and middle-income countries in Africa, Asia, and Latin America, and found statistically significant employment gaps for people with disabilities in nine out of the fifteen examples; interestingly, the six countries that had either no gap or a statistically insignificant gap were low-income nations, while all but two with a significant employment gap were middle-income.…”
Section: Global Situation Of Work and Economic Disparities For Peoplementioning
confidence: 99%
“…Mizunoya and Mitra (2013) assessed the employment gaps in fifteen low-and middle-income countries in Africa, Asia, and Latin America, and found statistically significant employment gaps for people with disabilities in nine out of the fifteen examples; interestingly, the six countries that had either no gap or a statistically insignificant gap were low-income nations, while all but two with a significant employment gap were middle-income.…”
Section: Global Situation Of Work and Economic Disparities For Peoplementioning
confidence: 99%
“…Yet, where data exist, individuals with disabilities are found to be disadvantaged in both accessing and sustaining work and other forms of economic activity. Employment participation rates for people with disabilities are below that of the overall population; and, when disabled people do work, they generally do so for longer hours and lower incomes, have fewer chances of promotion, are more likely to work in the informal labour market, and are at greater risk of becoming unemployed for longer periods (Coleridge, 2005;Contreras, Ruiz-Tagle, Garces, & Azocar, 2006;Houtenville, Stapleton, Weathers, & Burkhauser, 2009;Mete, 2008;Mitra, 2008;Mitra et al, 2013;Mitra & Sambamoorthi, 2006;Mizunoya & Mitra, 2012;Roulstone, 2012;Roulstone, Gradwell, Price, & Child, 2003). Using data from 27 countries, a recent study from the Organization for Economic Co-operation and Development (OECD) found that people with disabilities are half as likely to be in paid work as their non-disabled counterparts (44% compared with 75%) (OECD, 2010).…”
Section: Rationalementioning
confidence: 99%
“…Finally, Mizunoya and Mitra (2013) investigated the situation in developing countries. All of these studies found a negative impact of disability on employment (or labor market participation); the magnitude of which varies across countries and gender.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the income effects related to the reception of disability benefits, the substitution effect deriving from the higher opportunity costs of working that are associated with disabilities, and lower job-search intensity due to higher mobility costs decrease the labor supply of disabled people. In addition, special time requirements for self-care/rehabilitation activities associated with disability increase the marginal utility of leisure, decreasing the labor supply of disabled people (Mizunoya and Mitra 2013). Finally, from a demand-side perspective, employers would be less likely to hire disabled people because of their suspected lower productivity, the additional costs of adjusting workplaces to meet disability requirements, and prejudice and/or discrimination.…”
Section: Introductionmentioning
confidence: 99%